PENINGKATAN NILAI KALOR BIOBRIKET CAMPURAN SEKAM PADI DAN DOMINANSI KULIT KACANG METE DENGAN METODE PIROLISA - Onky Eridhani; Arijanto Arijanto; Muchammad Muchammad (JURNAL TEKNIK MESIN, 2013)
The requirement of fuel in Indonesia has increased recently. It needs an alternative fuel in order to increase the production of energy resources. One of the alternative energy sources is biomass. The materials to create biomass in Indonesia are rice husk, cocoa shell, and cashew shell. From these materials, biomass then is formed into biobriquette to increase mass density. The objective of this research is knowing the influence of pyrolysis process against the increasing of biobriquette heat value and knowing the comparison of the best heat value result of biobriquette composition 75% cashew shell – 25% rice husk from Torrefaction and the different pyrolysis method. Biobriquette which is used is made from the mixture of rice husk and cashew shell. Pyrolysis is a chemical putrefaction process from organic substance with high heating temperature within 300 ⁰C – 500 ⁰C. The research was held by using biobriquette composition 50% cashew shell – 50% rice husk, 75% cashew shell – 25% rice husk, and 100% cashew shell with mass percentage. Those materials of biobriquette are blended, and then bonded with PVA glue, and after that it was formed into briquette with 25 – 30 mm height and diameter is 25 mm. And then, the briquettes are pyrolized by temperature of 350, 400, and 450 ⁰C with a varied holding time within 15, 30, and 45 minutes. The result of this research is all of those variations can increase the heat value of biobriquette. The highest heat value result of biobriquette from these 3 compositions occured at the composition of biobriquette 100% cashew shell which was tested at the temperature of 450 ⁰C with the holding time at 30 minutes is 7233,1 call/g. However, The biobriquette’s mass had also decreased by the amount of 63,38% from the former weight 9,9 gram. From torrefaction and pyrolysis method with different variation which had ever been done before, biobriquette with the composition of 75% cashew shell – 25% rice husk at this pyrolysis test produced the highest heat value, that is 6407,6 call/g.